Kekerasan Simbolik (Studi Relasi Pendidik Dan Peserta Didik ) - Rina Oktafia Putri (IAIN Padangsidimpuan, 2019)
The background of this research is the existence of the symbolic domain, related between the teacher and the student. The symbolic violence that occurs is not expelled from the dynamics of education in Indonesia. This case is encouraged by the domination’s role, capital, domain, habitus which owned by an educator. Furthermore, the form of symbolic violence works through the mechanism of aufernisasi and sensorisasi, and it happened in the relation of the teacher and student. The symbolic violence is not something easy to be known, because it is running by the symbols of the discourse which the student areas the hegemony object, that is dominated by the produced meaning, based the domain of the subject, who has the domination. This research is a discourse analysis study, and the data is compelled by the verbal communication through the observation, the note, and the record. The result of this research is found that in the learning process, the student is headed in a single space and imposed to obey the rules of the educator. indeed, this relation is normal case, however, in this situation, the awareness is necessary for that it potentially become the symbolic violence.